Financial statecraft and transaction costs: The case of renminbi internationalization - Marina Zucker Marques (Freie Universität Berlin, School of Business & Economics, 2021)
The scholarly debate on currency internationalization focuses on country characteristics and policies as the main determinants in currency competition. However, this literature has neglected the fact that, given the intertwined nature of the international monetary system, other countries' actions and the functioning logic of international finance can also impact a currency's international status. This article shows that RMB usage has been boosted not only by Chinese statecraft but also by economic actors' recent difficulties in using the dollar. The American financial sanctions against Chinese trade partners, the cyclical instability of international finance, as well as peripheral countries' low inflows of dollars have encouraged firms and banks to use the renminbi as an alternative to the dollar. In addition to contributing to a broader understanding of the drivers of currency internationalization, this article proposes a model that explains the mechanisms that push firms and banks away from the incumbent international currency. I posit that changes in domestic and international conditions influence currency transaction costs, thereby propelling economic actors to increase their use of currencies with relatively lower transaction costs. Interviews with Chinese senior officials from the PBOC and the Ministry of Commerce, manufacturing companies, and bank staff are the main primary sources for this article. I triangulate this information with news reports and speeches both in Chinese and English.
urn:nbn:de:kobv:188-refubium-30516-1; hdl:10.17169/refubium-30256
Keywords: 330; international monetary system; renminbi internationalization; financial statecraft; dollar; currency competition